2019
DOI: 10.1016/j.molliq.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water/carbon interaction strength on interfacial thermal resistance and the surrounding molecular nanolayer of CNT and graphene flake

Abstract: Heat transfer at the liquid/solid interface, especially at the nanoscale, has enormous importance in nanofluids. This study investigates liquid/solid interfacial thermal resistance and structure of the formed molecular nanolayer around a carbon-based nanoparticle. Employing non-equilibrium molecular dynamics simulation and thermal relaxation method, the nanofluid systems with different nanoparticle diameters and different surface wettability were investigated. Simulation results show that carbon nanotubes (CNT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…of the order of 0.9 nm. As for the CNT -distilled-water nanofluid, molecular dynamics [64] predicts a density attaining the mean value of that of water outside a layer thickness of 1.2 nm. For a graphene -water nanofluid the same molecular dynamics study shows a value of 0.9 nm [64], confirmed by potential-energy profiles [65].…”
Section: Asymptotic Casesmentioning
confidence: 97%
See 1 more Smart Citation
“…of the order of 0.9 nm. As for the CNT -distilled-water nanofluid, molecular dynamics [64] predicts a density attaining the mean value of that of water outside a layer thickness of 1.2 nm. For a graphene -water nanofluid the same molecular dynamics study shows a value of 0.9 nm [64], confirmed by potential-energy profiles [65].…”
Section: Asymptotic Casesmentioning
confidence: 97%
“…As for the CNT -distilled-water nanofluid, molecular dynamics [64] predicts a density attaining the mean value of that of water outside a layer thickness of 1.2 nm. For a graphene -water nanofluid the same molecular dynamics study shows a value of 0.9 nm [64], confirmed by potential-energy profiles [65]. Neglecting the effect of inner graphite layers, we assume that the same layer thickness would occur for the graphite -water nanodispersion, i.e.…”
Section: Asymptotic Casesmentioning
confidence: 97%
“…The transport of water through CNTs has drawn significant attention due to their broad range of applications such as water desalination, drug delivery, hydrogen storage, etc. In addition to that, the higher Kapitza resistance between water and CNTs can be utilized for effectively transporting liquids at temperatures higher/lower than the ambient temperatures in future nanoscale devices for heating/cooling purposes at specific locations. Studies based on Kapitza resistance in CNT systems were mostly focused on nanocomposites and CNT-based bulk nanofluid systems. However, studies on the nanoconfinement effect on Kapitza resistance in systems with water filled inside a CNT and molecular dynamics methods to compute the Kapitza resistance inside such cylindrical nanoconfinement systems are seldom reported to the best of the authors’ knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…It shows that a better vibrational coupling between water and CNT at higher diameters, which increases the interface heat transfer, leads to a reduced Kapitza resistance. Jabbari et al 9 reported an increase in the Kapitza resistance with an increase in the CNT diameter in a water−CNT nanofluid system, where the water is outside the CNT. This can also be explained in terms of the area density factor.…”
mentioning
confidence: 99%
“…In addition, it was shown that the local thermal conductivity of the aqueous shell adjacent to the nanoparticle is approximately 50% higher than in volumetric water [ 57 ]. The calculations were made for metal particles [ 56 , 57 ] and systems containing graphene (4∙10 −8 m 2 K W −1 ) [ 55 , 58 ] and carbon nanotubes [ 59 ].…”
Section: Discussionmentioning
confidence: 99%